2017
DOI: 10.1590/2179-8087.140415
|View full text |Cite
|
Sign up to set email alerts
|

Estimação do Volume de Eucaliptos por Krigagem e Cokrigagem no Semiárido Pernambucano

Abstract: RESUMOOs volumes de 1875 árvores de um plantio de eucalipto foram rigorosamente cubadas pelo processo de Smalian, conhecendo-se assim o volume total do plantio que é de 166,14 m 3 . As árvores foram localizadas em um plano cartesiano (X, Y) e duas técnicas geoestatísticas foram aplicadas: a krigagem e cokrigagem. Para a cokrigagem foi utilizada como variável secundária o diâmetro a altura do peito (DAP), variável com alta correlação com o volume de madeira (Vol) do eucalipto. Três tamanhos de amostras foram re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Some studies have confirmed the strong spatial dependence of the dominant height in commercial stands of Eucalyptus sp. (MELLO et al, 2005;GUEDES et al, 2015;LUNDGREN et al, 2017;ATAÍDE et al, 2020). In addition, the regression models provide the average estimate of growth in dominant height and allow site index estimates only in places where there was a measured sample unit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have confirmed the strong spatial dependence of the dominant height in commercial stands of Eucalyptus sp. (MELLO et al, 2005;GUEDES et al, 2015;LUNDGREN et al, 2017;ATAÍDE et al, 2020). In addition, the regression models provide the average estimate of growth in dominant height and allow site index estimates only in places where there was a measured sample unit.…”
Section: Introductionmentioning
confidence: 99%
“…stands, as well as to other species, for example, Pinus sp. and Tectona grandis (MELLO et al, 2005;PELISSARI et al, 2014;GUEDES et al, 2015;PELISSARI et al, 2015;LUNDGREN et al, 2017;ZECH et al, 2018;ATAÍDE et al, 2020). Even with numerous studies evaluating the spatial structuring of dendrometric variables, few use the site index variable, mainly when obtained by mathematical models.…”
Section: Introductionmentioning
confidence: 99%